Advisory Committee on Animal Husbandry and Dairying Volume II-B [ Filled Format for Information on Animal Husbandry and Dairy Sector submitted by States/UT'S ] - Planning Commission (Planning Commission, 2010)
What is the role of AH department in the process of formulating the overall District Perspective plans ? this may be specified are the AH Department being effectively heard and taken cognizance of by the DPC while finalizing the District plan? If not, the mechanism to be adopted for effective role of Department in the planning process may be indicated. While formulating the overall District Perspective plans, proposals of A.H.Dept. are being effectively heard and taken cognizance of by the DPC.
Planning Commission, Government of India